Sclerostin neutralization unleashes the osteoanabolic effects of Dkk1 inhibition - Witcher, Phillip C. (JCI Insight, 2018)
The WNT pathway has become an attractive target for skeletal therapies. High-bone-mass phenotypes in patients with loss-of-function mutations in the LRP5/6 inhibitor Sost (sclerosteosis), or in its downstream enhancer region (van Buchem disease), highlight the utility of targeting Sost/sclerostin to improve bone properties. Sclerostin-neutralizing antibody is highly osteoanabolic in animal models and in human clinical trials, but antibody-based inhibition of another potent LRP5/6 antagonist, Dkk1, is largely inefficacious for building bone in the unperturbed adult skeleton. Here, we show that conditional deletion of Dkk1 from bone also has negligible effects on bone mass. Dkk1 inhibition increases Sost expression, suggesting a potential compensatory mechanism that might explain why Dkk1 suppression lacks anabolic action. To test this concept, we deleted Sost from osteocytes in, or administered sclerostin neutralizing antibody to, mice with a Dkk1-deficient skeleton. A robust anabolic response to Dkk1 deletion was manifest only when Sost/sclerostin was impaired. Whole-body DXA scans, μCT measurements of the femur and spine, histomorphometric measures of femoral bone formation rates, and biomechanical properties of whole bones confirmed the anabolic potential of Dkk1 inhibition in the absence of sclerostin. Further, combined administration of sclerostin and Dkk1 antibody in WT mice produced a synergistic effect on bone gain that greatly exceeded individual or additive effects of the therapies, confirming the therapeutic potential of inhibiting multiple WNT antagonists for skeletal health. In conclusion, the osteoanabolic effects of Dkk1 inhibition can be realized if sclerostin upregulation is prevented. Anabolic therapies for patients with low bone mass might benefit from a strategy that accounts for the compensatory milieu of WNT inhibitors in bone tissue.